Security Issues in Grid Computing: Ensuring Secure Grid Computing with Advanced Technologies (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Grid computing is concerned with the sharing and use of resources in dynamic distributed virtual organizations. The dynamic nature of Grid environments introduces challenging security concerns that demand new technical approaches. In this brief overview we review key Grid security issues and outline the technologies that are being developed to address those issues. We focus on works done by Globus Toolkits to provide security and also we will discuss about the cyber security in Grid.